Human embryonic stem cells and good manufacturing practice: Report of a 1- day workshop held at Stem Cell Biology Research Center, Yazd, 27th April 2017 - Fatemeh Akyash; Fatemeh Sadeghian-Nodoushan; Somayyeh Sadat Tahajjodi; Habib Nikukar; Ehsan Farashahi Yazd; Mostafa Azimzadeh; Harry D. Moore; Behrouz Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2017)
This report explains briefly the minutes of a 1-day workshop entitled; "human embryonic stem cells (hESCs) and good manufacturing practice (GMP)" held by Stem Cell Biology Research Center based in Yazd Reproductive Sciences Institute at Shahid Sadoughi University of Medical Sciences, Yazd, Iran on 27th April 2017. In this workshop, in addition to the practical sessions, Prof. Harry D. Moore from Centre for Stem Cell Biology, University of Sheffield, UK presented the challenges and the importance of the biotechnology of clinical-grade human embryonic stem cells from first derivation to robust defined culture for therapeutic applications.